A STUDY ON THE PROTECTION OF FOOD ART UNDER COPYRIGHT ACT,1957 (International Journal of Food and Nutritional Sciences, 2022)
It is become the routine activity to dine out in the present time. The people involved in this business of food such as the chef and the restaurant owners are trying to improve the dining experience of the consumers. The chef are considered as the artist who prepare the food with an eye tempting presentations. The process of arrangement of the food by the chef is only done with the help of human intellect. The chef presents their food presentation with the help of colour combinations, placing the food by working for many hours. This process of presentation involves the creativity and the skill of the chef. But in the present time, this skill of presentation needs legal protection. This research paper is trying to examine whether the restaurant owners and the chefs can protect their food creation or the food art under the present copyright law.